KETAHANAN TERIMBAS TANAMAN CABAI MERAH TERHADAP PENYAKIT ANTRAKNOSA MELALUI INDUSER MIKORIZA INDIGENUS - Mulyani R. B.; Sastrahidayat I. R.; Abadi A. L.; Djauhari S (Fakultas Pertanian Universitas Palangka Raya, 2016)
The high intensity of anthracnose disease in the peat swamp area in Palangka Raya has consequently forced the farmers to expend higher costs for controlling and coping the disease using synthetic fungicides. The aim of this study was to investigate the role of indigenous mycorrhiza on the induce resistance structural and chemical resistance of red chili plant and to reduce the intensity of anthracnose disease. This study was performed by using a randomized complete design method, which was arranged into two treatment groups in three independent repeats. The treatment factors were classified as follows: 1) the application of indigenous mycorrhiza (M), which was divided into two subgroups: M0 (without mycorrhiza) and M1 (with mycorrhiza); and 2) the different doses of weed ash (A), which consisted of A0 (without ash), A1 (with 200 g of ash), A2 (with 250 g of ash), and A3 (with 300 g of ash). Plants without mycorrhiza and without ash administration served as controls. The result of this study showed that the usage of mycorrhiza with 250 g of ash per plant could reduce 49.2% of anthracnose disease intensity, increase total phenol level amount 68,4% and the thickness of the fruit cuticle amount 49,8% compared to control groups. In conclusion, the application of mycorrhiza is beneficial to induce resistance the total phenol level and fruit cuticle thickness; therefore it subsequently might increase the resistance of the plant to the anthracnose disease